Reduction in the Dietary VA Status Prevents Type 2 Diabetes and Obesity in Zucker Diabetic Fatty Rats - Tiannan Wang; Xia Tang; Xinge Hu; Jing Wang; Guoxun Chen (Biomolecules, 2022)
We hypothesized that the vitamin A (VA) status regulates type 2 diabetes (T2D) development in Zucker diabetic fatty (ZDF) rats. Zucker Lean and ZDF rats at weaning were fed a VA deficient with basal fat (VAD-BF, no VA and 22.1% fat energy), VA marginal with BF (VAM-BF, 0.35 mg retinyl palmitate (RP)/kg), VA sufficient with BF (VAS-BF, 4.0 mg RP/kg), VAD with high fat (VAD-HF, 60% fat energy), VAM-HF or VAS-HF diet for 8 weeks, including an oral glucose tolerance test (OGTT) at week 7.5. The hepatic mRNA and proteins levels were determined using real-time PCR and Western blot, respectively. The VAD-BF/HF and VAM-BF/HF diets prevented peripheral hyperglycemia and attenuated obesity in ZDF rats, which occurred in the presence of the VAS-BF/HF diets. This lowered VA status reduced venous blood hyperglycemia, hyperinsulinemia and hyperlipidemia, and improved OGTT and homeostasis model assessment for insulin resistance results in ZDF rats. The expression levels of key hepatic genes for glucose and fat metabolism were regulated by VA status and dietary fat contents. An interaction between VA and HF condition was also observed. We conclude that the reduction in the dietary VA status in both BF and HF conditions prevents T2D and obesity in ZDF rats.